Inflammatory profile of apical periodontitis exacerbated by cigarette smoke inhalation: Histological and immunohistochemical analysis in rats - Vasques, Ana Maria Veiga [UNESP]; da Silva, Ana Claudia Rodrigues [UNESP]; Bueno, Carlos Roberto Emerenciano [UNESP]; Cury, Marina Tolomei Sandoval [UNESP]; Ervolino, Edilson [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Dezan Junior, Eloi [UNESP] (Wiley, 2023)
Aim: The aim of this study was to evaluate the effects of cigarette smoke inhalation (CSI) on inflammation, pro-inflammatory mediators and haematological parameters in rats with induced apical periodontitis (AP). Methodology: Thirty-two 3-month-old male Wistar rats were divided into four experimental groups (n = 8): C—Control; S—rats with CSI; AP—rats with AP; and SAP—rats with CSI + AP. Animals in groups S and SAP inhaled cigarette smoke by remaining inside a smoking chamber for 8 min, three times daily, for 50 days. After 20 days of smoke inhalation, animals in AP and SAP groups had the pulps of the lower right first molar exposed to oral environment for 30 days to induce AP. In these subsequent 30 days, animals in group S and SAP continued with CSI. On Day 50, animals were euthanized and mandibles were histologically processed to assess inflammatory infiltrate, immunohistochemical interleukins (IL-1β, IL-6 and TNF-α), and blood samples collected for laboratory analysis. The Mann–Whitney test was performed for non-parametric data and the pairwise analyses of Student's t-test for parametric data, with a significance level of p <.050. Results: Inflammatory infiltrate was moderate in AP group and more severe in the SAP (p =.010). The interleukins IL-6, IL-1β and TNF-α were higher in SAP group (p <.001) when compared to the AP group. A greater number of red blood cells (p =.010), haemoglobin (p =.007) and neutrophils (p =.014) were observed in the SAP group in comparison with the AP group. Conclusion: Cigarette smoke inhalation induced a more severe inflammatory infiltrate, with increased levels of pro-inflammatory cytokines and changes in haematological parameters in rats with induced AP. Thus, CSI aggravated AP, exacerbating the inflammatory response.
Keywords: animal model; apical periodontitis; endodontics; inflammation; oral infections; smokers